2021
DOI: 10.21203/rs.3.rs-344039/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Percutaneous Absorption Enhancer Properties of Lavandula Angustifolia Essential Oil on Percutaneous Absorption of Naproxen Sodium from Topical Gel

Abstract: The naproxen bioavailability via percutaneous route is low, and several technologies have been used to overcome the problem. Although the permeation enhancer properties of natural essential oils have been reported, there is no study to show the effectiveness of Lavandula angustifolia essential oil on the percutaneous absorption of naproxen sodium from a topical gel to overcome poor percutaneous absorption of naproxen. To this end, the naproxen topical gel was formulated using Carbopol 940 (as a gelling agent),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The use of this oil formulation allowed the API to be delivered to the skin at a higher concentration (222.19 ± 24.87 μg/cm 2 ) compared to naproxen gel alone (107.65 ± 6.38 μg/cm 2 ). The main constituents of lavender oil, as confirmed by gas chromatography–mass spectrometry (GC-MS) analysis included 1,8-cineole (22.3%), linalool (11.2%), camphor (7.9%), β-pinene (5.8%), α-terpineol (4.9%), α-pinene (4.6%), terpinen-4-ol (4.2%), and borneol (4.0%) . An in vitro rat skin permeation study showed that essential oils at a concentration of 3% extracted from Radix Angelicae sinensis [ Angelica sinensis (Oliv.)…”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 98%
See 2 more Smart Citations
“…The use of this oil formulation allowed the API to be delivered to the skin at a higher concentration (222.19 ± 24.87 μg/cm 2 ) compared to naproxen gel alone (107.65 ± 6.38 μg/cm 2 ). The main constituents of lavender oil, as confirmed by gas chromatography–mass spectrometry (GC-MS) analysis included 1,8-cineole (22.3%), linalool (11.2%), camphor (7.9%), β-pinene (5.8%), α-terpineol (4.9%), α-pinene (4.6%), terpinen-4-ol (4.2%), and borneol (4.0%) . An in vitro rat skin permeation study showed that essential oils at a concentration of 3% extracted from Radix Angelicae sinensis [ Angelica sinensis (Oliv.)…”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 98%
“…The main constituents of lavender oil, as confirmed by gas chromatography–mass spectrometry (GC-MS) analysis included 1,8-cineole (22.3%), linalool (11.2%), camphor (7.9%), β-pinene (5.8%), α-terpineol (4.9%), α-pinene (4.6%), terpinen-4-ol (4.2%), and borneol (4.0%). 67 An in vitro rat skin permeation study showed that essential oils at a concentration of 3% extracted from Radix Angelicae sinensis [ Angelica sinensis (Oliv.) Diels ( Umbelliferae )], Rhizoma chuanxiong [ Ligusticum chuanxiong Hort.…”
Section: Natural Compounds With the Penetration-enhancing Potential O...mentioning
confidence: 99%
See 1 more Smart Citation